Faktor risiko gizi kurus pada anak sekolah dasar Negeri Kulam Data Kecamatan Lhoknga Kabupaten Aceh Besar - Cut Affianijar; Agus Hendra Al Rahmad; Alfridsyah Alfridsyah; Suryana Suryana (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Wasting is nutritional status in school children. In the community it is known as thin nutrition which is an important public health problem because it has a big impact. Thin nutrition can increase the risk of illness and death in children.Objectives: To determine the risk factors for wasting nutrition in children of Kulam Data Elementary School in Lhoknga District.Methods: This study is descriptive analytic with cross-sectional research design. The number of samples is 57 people. The research variables consisted of diet, energy intake, protein intake and nutritional status with the incidence of wasting nutrition in school children in Kulam Data Elementary School Lhoknga District. Aceh Besar District. The study was conducted in June 2019. Data analysis used a chi-square test with a desired level of confidence of 95%. Research data is presented in tabular and textual forms.Results: The results of the study showed that more energy intake was in the sufficient category (84.4%). While the diversity of food consumption is more in the medium category which is equal to 64.7%. There is an influence between energy intake on the incidence of wasting nutrition in school children (p= 0.022) and there is an influence between the diversity of food consumption on the incidence of wasting in school children (p= 0.041).Conclusion: Regarding energy intake, the diversity of food consumption with balanced wasting nutrition. To avoid malnutrition, treatment is needed from the school, health center, and parents. This is necessary so that children can meet the nutritional needs of energy sources, proteins, fats in accordance with the portion of balanced nutrition.